Bus Implementation Using New Low Power PFSCL Tristate Buffers. (29th February 2016) - Pandey, Neeta; Choudhary, Bharat; Gupta, Kirti; Mittal, Ankit
Abstract : This paper proposes new positive feedback source coupled logic (PFSCL) tristate buffers suited to bus applications. The proposed buffers use switch to attain high impedance state and modify the load or the current source section. An interesting consequence of this is overall reduction in the power consumption. The proposed tristate buffers consume half the power compared to the available switch based counterpart. The issues with available PFSCL tristate buffers based bus implementation are identified and benefits of employing the proposed tristate buffer topologies are put forward. SPICE simulation results using TSMC 180 nm CMOS technology parameters are included to support the theoretical formulations. The performance of proposed tristate buffer topologies is examined on the basis of propagation delay, output enable time, and power consumption. It is found that one of the proposed tristate buffer topology outperforms the others in terms of all the performance parameters. An examination of behavior of available and the proposed PFSCL tristate buffer topologies under parameter variations and mismatch shows a maximum variation of 14%.